2008
DOI: 10.1016/j.jneumeth.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

An auditory brain–computer interface (BCI)

Abstract: Brain-computer interfaces (BCIs) translate brain activity into signals controlling external devices. BCIs based on visual stimuli can maintain communication in severely paralyzed patients, but only if intact vision is available. Debilitating neurological disorders however, may lead to loss of intact vision. The current study explores the feasibility of an auditory BCI. Sixteen healthy volunteers participated in three training sessions consisting of 30 2-3 min runs in which they learned to increase or decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
262
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(268 citation statements)
references
References 14 publications
5
262
0
1
Order By: Relevance
“…Nijboer et al [31,32] showed that five out of six patients affected by Motor Neuron Disease or Amyotrophic Lateral Sclerosis (ALS) could use the P3-based BCI for communication after one training session. Thereafter, four of them continued using it for functional communication in a second phase of the study, and all were able to spell messages of considerable length when more features were extracted from the EEG [32].…”
Section: P3-based Bcismentioning
confidence: 99%
“…Nijboer et al [31,32] showed that five out of six patients affected by Motor Neuron Disease or Amyotrophic Lateral Sclerosis (ALS) could use the P3-based BCI for communication after one training session. Thereafter, four of them continued using it for functional communication in a second phase of the study, and all were able to spell messages of considerable length when more features were extracted from the EEG [32].…”
Section: P3-based Bcismentioning
confidence: 99%
“…By providing feedback of cortical activity, neuroplasticity can be induced which could potentially impart therapeutic benefits on sensorimotor function. BMI training paradigms have been used to induce motor-related neuroplasticity by providing direct neural feedback of individual's brain activity (Gage et al 2005;Nijboer et al 2008;Hochberg et al 2006;Helms Tillery et al 2003;Buch et al 2008;Mellinger et al 2007). Some work has been done directly with individuals with paralysis as a proof-of-concept for using MEG as rehabilitation therapy.…”
Section: Neurofeedback Therapies For Physical Rehabilitationmentioning
confidence: 99%
“…Therefore, the P300 can be used in a BCI that automatically detects which stimuli elicited a P300, and thus which stimuli (such as letters) the user wants to communicate. The P300 was first used in a BCI almost 30 years ago (Farwell and Donchin, 1988), and has been validated in ALS patients (Kübler et al, 2001;Sellers and Donchin, 2006;Nijboer et al, 2008a;Fazel-Rezai et al, 2012;Marchetti and Priftis, 2014). Surveys of ALS patients who used the system, and related work, found that some patients were happy with the functionality provided by the BCI, but many had concerns that included robustness and flexibility (Kathner et al, 2015;Pasqualotto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%